Progranulin Preserves Autophagy Flux and Mitochondrial Function in Rat Cortical Neurons Under High Glucose Stress - Dedert, Cass; Mishra, Vandana; Aggarwal, Geetika; Nguyen, Andrew D.; Xu, Fenglian (Frontiers in Cellular Neuroscience, 2022)
Chronic hyperglycemia in type II diabetes results in impaired autophagy function, accumulation of protein aggregates, and neurodegeneration. However, little is known about how to preserve autophagy function under hyperglycemic conditions. In this study, we tested whether progranulin (PGRN), a neurotrophic factor required for proper lysosome function, can restore autophagy function in neurons under high-glucose stress. We cultured primary cortical neurons derived from E18 Sprague-Dawley rat pups to maturity at 10 days in vitro (DIV) before incubation in high glucose medium and PGRN for 24-72 hours before testing for autophagy flux, protein turnover, and mitochondrial function. We found that although PGRN by itself did not upregulate autophagy, it attenuated impairments in autophagy seen under high-glucose conditions. Additionally, buildup of the autophagosome marker light chain 3B (LC3B) and lysosome marker lysosome-associated membrane protein 2A (LAMP2A) changed in both neurons and astrocytes, indicating a possible role for glia in autophagy flux. Protein turnover, assessed by remaining advanced glycation end-product levels after a six-hour incubation, was preserved with PGRN treatment. Mitochondrial activity differed by complex, although PGRN appeared to increase overall activity in high glucose. We also found that activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and glycogen synthase kinase 3β (GSK3β), kinases implicated in autophagy function, increased with PGRN treatment under stress. Together, our data suggest that PGRN prevents hyperglycemia-induced decreases in autophagy by increasing autophagy flux via increased ERK1/2 kinase activity in primary rat cortical neurons.